The Effect of Taxpayer Knowledge, Taxpayer Awareness, and Tax Sanctions on Corporate Taxpayer Compliance at KPP Pratama South Bekasi - Lisdawati Arifin; Pandu Perdana Saputra; Rianto Rianto (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
Taxes are the country's largest source of financing in administering the government. The role of taxes is increasingly strategic, especially during the current weakening economic conditions. Tax compliance is a condition where the taxpayer fulfills all tax obligations and exercises tax rights. It is necessary to increase the compliance of taxpayers to comply with their obligations by coercive and continuous efforts by the government so that the tax revenue target is achieved according to the predetermined target. The purpose of this study was to determine the effect of taxpayer knowledge, taxpayer awareness, tax sanctions, on corporate taxpayer compliance at KPP Pratama Bekasi Selatan, was studied using a quantitative approach with an associative descriptive research design. The population in this study were corporate taxpayers registered at the KPP Pratama, South Bekasi. Sampling using incidental sampling technique with a sample of 100 respondents, data was collected by distributing questionnaires, anyone who coincidentally met with the researcher could be used as a sample, if deemed suitable as a data source. The results showed that the knowledge of taxpayers had a positive and significant effect on corporate taxpayer compliance, this was evidenced by the positive regression coefficient value of 0.427 and tcount of 4.754 > t table 1983 at a significance of 0.000 <0.05. Taxpayer awareness has a positive and significant effect on corporate taxpayer compliance, this is evidenced by the positive value of the regression coefficient, namely 0.352 and t count of 4.086 > t table 1.983 at a significance of 0.000 <0.05. Tax sanctions have a positive and significant effect on corporate taxpayer compliance, this is evidenced by the positive value of the regression coefficient, namely 0.515 and t arithmetic of 6.066 > t table 1983 at a significance of 0.000 < 0.05. Taxpayer knowledge, taxpayer awareness, and tax sanctions have a positive and significant effect together, this is evidenced by the positive value of the regression coefficient, namely 0.225, 0.231, 0.382 and Fcount of 21.082 > Ftable 3.09.